Palladium chloride catalyzed photochemical heck reaction - Waghmode, Suresh B.; Arbuj, Sudhir S.; Wani, Bina N.; Gopinath, Chinnakonda S. (Canadian Journal of Chemistry-Revue Canadienne De Chimie, 2013)
PdCl2 catalyzed carbon-carbon bond formation (Heck reaction) between substituted aryl halides and olefins was carried out without a ligand, under irradiation with UV-visible light. The results demonstrated that UV-visible light accelerated the rate of the reaction, leading to an excellent yield of corresponding products. The recovered palladium nanoparticles could be thermally recycled several times. PdCl2 gave excellent conversion up to the fifth addition of substrate.
Keywords: C-C coupling; Heck reaction; iodobenzene; photochemical reaction